Brain Tumors in Children (Springer International Publishing, 2018)
This book is a comprehensive and up-to-date compendium of all aspects of brain tumors in children. After introductory chapters on the epidemiology of brain tumors, the book will provide readers with state-of-the art chapters on the principals of radiation therapy, neurosurgery and neuroimaging. Subsequent chapters discuss the biology and treatment of specific types of brain tumors. The concluding chapters present critical information relevant to survivorship, neurocognitive and other late effects, and the global challenges to better diagnosis and treatment of brain tumors in children. This book is co-authored by experts in the treatment of pediatric brain tumors. All of the authors are internationally recognized authorities and they offer an evidence-based consensus on the biology and treatment of brain tumors. This handbook has far-reaching applicability to the clinical diagnosis and management of brain tumors in children and will prove valuable to specialists, generalists and trainees alike.